Taekwondo sports coaching at Mahameru Club: A basic interpretive study on historical aspects, coaching systems, management resources, and achievement coaching - Setyasih, Nur; Sugiyanto; Liskustyawati, Hanik; Riyadi, Slamet (Journal Sport Area, 2023)
The Taekwondo sports coaching system necessitates effective organisational management. However, managing a sports organisation unquestionably demands a suitable and accurate concept, one that will ultimately allow the sports organisation to accomplish its objectives. The purpose of this study was to examine the basic interpretation of historical aspects, development systems, management resources, and achievement development. The research method used in this study is qualitative descriptive research, employing a phenomenological research design. The research sample consists of 5 informants, including 1 club founder, 2 club executives, and 2 athlete coaches, selected for direct interviews. Data analysis involves (i) introduction and organization; (ii) coding and reduction; (iii) interpretation and representation. The findings revealed that the coaching system, management resources and Taekwondo achievement development at the Mahameru Club in Sukoharjo Regency were functioning effectively. The limitations of this study are the sample used and the scope of the study which is only one area. As a result, future research should compare and broaden the scope of the study by investigating the factors that influence the implementation of the coaching system, management resources, and achievement development, such as psychological, sociological, and environmental aspects for athletes. The conclusion of this research indicates that this research makes a notable contribution by delving into the uncharted territory of Taekwondo sports coaching at Mahameru Club. It not only fills a knowledge gap but also furnishes practical guidance for the improvement of coaching strategies.